The experience of using a bacteriophages-based complex antibacterial and analgesic drug in gel formulation in women who underwent various instrumental and diagnostic and treatment interventions - Alexander O. Vasilyev; Natalia A. Sazonova; Vladimir D. Melnikov; Amir F. Gabdullin; Andrei V. Zaitsev; Arseniy A. Shiryaev; Yuriy A. Kim; Elena A. Prilepskaya; Dmitry Yu. Pushkar (IP Berlin A.V., 2020)
During the spread of bacterial infections with extensive drug resistance, the potential of existing antibacterial drugs is significantly reduced. The medical community is seeking opportunities for the rational use of antibacterial drugs, the development of new drugs, as well as the use of alternative treatments for these infections. Aim. The objective of this study was to evaluate the effectiveness of the use of a complex antibacterial and analgesic drug based on bacteriophages in gel form during various instrumental studies and diagnostic procedures in order to minimize the risk of the urinary system infections complications. Materials and methods. The study included 235 women aged 18 to 75 years who underwent treatment at the Moscow State Clinical Hospital named after Spasokukotsky and in the clinic of urology of Moscow State University of Medicine and Dentistry from September 2019 to January 2020. During the manipulation, all patients of the main group (n=120) used a developed preparation based on bacteriophages, and in the control group (n=115), a topical gel based on chlorhexidine dihydrochloride and lidocaine hydrochloride was used. All patients before the manipulation, as well as 10 days after the manipulation, underwent bacteriological analysis of urine. Efficiency assessment was carried out on the basis of laboratory data obtained, as well as according to the visual analogue scale of the pain syndrome severity. Results. None of the patients in the main group showed intolerance, side effects and allergic reactions of the developed drug based on bacteriophages. Bacteriological analysis of urine received before manipulation in both groups showed the absence of clinically significant titers of pathogenic bacteria, while 1 week after manipulation the number of titers of pathogenic bacteria (104) was significantly higher in the control group (p0.04). In patients of the main group, the incidence of dysuria was lower compared with the control group (p0.05). Conclusion. The study showed good tolerance of the developed drug and its clinical effectiveness in reducing the number of symptomatic bacteriuria; severity of pain after undergoing manipulation was relatively lower in the main group of patients. Conducting multicenter studies with the inclusion of a larger number of patients in the future will reduce the economic costs associated with treating patients by reducing the number of cases of nosocomial infections and reducing postoperative time spent by patients in the hospital.